LANGUAGE TESTS AND THEIR ROLE IN SOCIETY - Koláčková, Ludmila; Šikolová, Mária (PEOPLE: International Journal of Social Sciences, 2021)
Being continually subjected to various forms of assessment remains a certainty for most of us, and the results of those evaluations often have a significant impact on our lives, be it positive or negative.Whether we have in mind aptitude tests, language tests, entrance examinations or either high school or a university, driving tests, their results are invariably of profound importance for us of profound importance for us. It is automatically taken for granted by the public is that the requirements for passing the tests are appropriate, and the instruments for the measurement of the required knowledge, abilities, performance, skills or competencies have been constructed in such a way that they reliably and accurately measure what they are intended to measure. Nevertheless, we often do not realize that this ideal is not always the case and hence, the tests frequently become a potentially dangerous instrument in the hands of the powerful in order to impose their policies. The objective of the contribution is to raise awareness and focus attention on the importance of tests, their design and quality control. It will illustrate the pitfalls in the area of language testing both from professional literature and authors’ experience.